2011
DOI: 10.1002/zoo.20395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential variables contributing to the development and duration of plantar lesions in a population of aquarium‐maintained African penguins (Spheniscus demersus)

Abstract: Bumblefoot (pododermatitis), often described as the most significant environmental disease of captive penguins, is commonly due to excessive pressure or trauma on the plantar surface of the avian foot, resulting in inflammation or necrosis and causing severe swelling, abrasions, or cracks in the skin. Although not formally evaluated in penguins, contributing factors for bumblefoot are thought to be similar to those initiating the condition in raptors and poultry. These factors include substrate, body weight, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Possible stress due to physical restraint can be minimized through conditioning of animals in permanent captivity [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible stress due to physical restraint can be minimized through conditioning of animals in permanent captivity [7].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, perfusion of the dermal tissues becomes compromised, which allows microorganisms to damage the dermis [6], leading to erosion and ulcer formation. Inappropriate environment and sedentary habits are therefore factors that may explain why this condition is one of the most frequent and important clinical complications in captive birds [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pododermatitis is commonly found in captivity and in rehabilitation centers, and an arsenal of drugs is traditionally used as an attempt to overcome it. Another factor involved in the severity of the disease is the high degree of infections recurrence; it is difficult to achieve perfect healing, which contributes to the difficulty of managing the disease [Erlacher‐reid et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…The severity of the disease can be classified into five stages that vary according to clinical aspects [Oaks, ]. These lesions are currently one of the most frequent and important clinical complications in seabirds kept in captivity or in rehabilitation centers [Erlacher‐reid et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Young (2003), showed that, in species such as penguins, the probability of the development of this disease can be reduced by lessen the pressure on the feet with the use of pebbles as substrates. According to Erlacher-Reid et al (2011), smooth flat substrates, such as concrete and increased weight are likely to increase pressure on the bony prominences and heels where lesions are usually located. The stimulation of their permanence in the water by their interaction with enrichment items showed to be effective in reducing bumblefoot lesions (4 in 5 penguins) throughout the 12 weeks of observations, showing to have a direct relation between the increase of time spent in the water and the decrease of lesions.…”
Section: Discussionmentioning
confidence: 99%